2020
DOI: 10.1111/pala.12514
|View full text |Cite
|
Sign up to set email alerts
|

Climatic drivers of latitudinal variation in Late Triassic tetrapod diversity

Abstract: The latitudinal biodiversity gradient (LBG), the increase in biodiversity from the poles to the equator, is one of the most widely recognized global macroecological patterns, yet its deep time evolution and drivers remain uncertain. The Late Triassic (237–201 Ma), a critical interval for the early evolution and radiation of modern tetrapod groups (e.g. crocodylomorphs, dinosaurs, mammaliamorphs), offers a unique opportunity to explore the palaeolatitudinal patterns of tetrapod diversity since it is extensively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 91 publications
5
41
0
Order By: Relevance
“…A recent study on the palaeobiogeographic distribution of Late Triassic tetrapods supported this idea for nonpseudosuchian archosaurs because they had a palaeobiogeographic distribution similar to that of extant endothermic animals (Dunne et al, 2020). By contrast, pseudosuchians were more diverse in warmer environments, as is the case for extant ectothermic reptiles (Dunne et al, 2020). This study also concluded that palaeoclimate could have had a direct influence on the distribution of species during that time span.…”
Section: Regla De Bergmannsupporting
confidence: 55%
See 1 more Smart Citation
“…A recent study on the palaeobiogeographic distribution of Late Triassic tetrapods supported this idea for nonpseudosuchian archosaurs because they had a palaeobiogeographic distribution similar to that of extant endothermic animals (Dunne et al, 2020). By contrast, pseudosuchians were more diverse in warmer environments, as is the case for extant ectothermic reptiles (Dunne et al, 2020). This study also concluded that palaeoclimate could have had a direct influence on the distribution of species during that time span.…”
Section: Regla De Bergmannsupporting
confidence: 55%
“…There is evidence for a relationship between body size and palaeolatitudinal variation, where the evolution of body size follows a punctuated model of evolution consistent with periods of environmental change, for crocodylomorphs (Stockdale & Benton, 2021). A recent study on the palaeobiogeographic distribution of Late Triassic tetrapods supported this idea for nonpseudosuchian archosaurs because they had a palaeobiogeographic distribution similar to that of extant endothermic animals (Dunne et al, 2020). By contrast, pseudosuchians were more diverse in warmer environments, as is the case for extant ectothermic reptiles (Dunne et al, 2020).…”
Section: Regla De Bergmannmentioning
confidence: 98%
“…In this vein, the recent report of metoposaurid “osteoderms” from Zimbabwe (~40°S) by Barrett et al (2020) warrants some discussion here. This is an intriguing novel occurrence, not yet addressed by temnospondyl workers, that has already been propagated by several studies (Dunne et al, 2020; Sciscio et al, 2020) and has been utilized as a line of evidence for broader claims, such as biome analogy with geographically disparate deposits (Barrett et al, 2020). However, there are several reasons to exercise caution with this purported occurrence.…”
Section: Discussionmentioning
confidence: 82%
“…Consequently, the mechanisms that contributed to the development of a metoposaurid zone of exclusivity by the latest Carnian (Otischalkian LVF) in North America remain unclear. Climatic variation along paleolatitudinal gradients (e.g., Sues and Olsen, 2015) and climatic instability (e.g., Whiteside et al, 2015) are popular hypotheses invoked for explaining the distribution of amniotes (e.g., Dunne et al, 2020), such as the absence of the herbivorous sauropodomorph dinosaurs, but hypotheses specifically regarding the distribution of large-bodied stereospondyls have not been formulated. A large body of recent work has emerged examining the role of the Carnian Pluvial Episode (CPE) in shaping terrestrial tetrapod evolution, but few have explicitly addressed temnospondyls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation